Chemical Engineering Processes Stability Theory - Christo Boyadjiev (Challenges and Advances in Chemical Science Vol. 1, 2021)
A theoretical analysis of the stability of the non-equilibrium chemical engineering processes is presented. A unified approach is proposed for the creation of the mathematical models of the systems that allows the determination of the velocities at which the systems move to their thermodynamic equilibriums and their use for mathematical analysis of systems velocities stability. For this purpose, is used mathematical stability theory, evolution (autonomous) equations, bifurcation theory (stable focuses, stable cycles), parameter eigenvalues and eigenfunctions.